Learning and Intelligent Optimization 9th International Conference, LION 9, Lille, France, January 12-15, 2015. Revised Selected Papers - Dhaenens, Clarisse.; Dhaenens, Clarisse.; Jourdan, Laetitia.; Jourdan, Laetitia.; Marmion, Marie-Eléonore.; Marmion, Marie-Eléonore. (Theoretical Computer Science and General Issues ;, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International Conference on Learning and Optimization, LION 9, which was held in Lille, France, in January 2015. The 31 contributions presented were carefully reviewed and selected for inclusion in this book. A large variety of topics are covered, such as benchmark problems and performance measures; tracking moving optima; dynamic multiobjective optimization; adaptation, learning, and anticipation; handling noisy fitness functions; using fitness approximations; searching for robust optimal solutions; comparative studies; hybrid approaches; theoretical analysis; and real-world applications.